COVID-19: Phenomenology of fear and hermeneutics of solidarity in the plague of Athens and in the contemporary pandemic (2021)
The main purpose of this article is to conduct an analysis of the current pandemic, attempting to locate basic layers of the phenomenon, in particular, the way its world is structured and the links of coexistence between individuals, taking as thread an element that analytics Heideggerian existentialism highlights as characteristic of man’s way of opening to the world: the emotional temper or affective disposition. To place this element and guide our questions, we will analyze Thucydides’ account of the plague that devastated Athens at the end of the fifth century BC. Starting with Thucydides’ indications, we will move toward the field of existential analytics to discover how worldly relations are defined in connection with the world from his approach. We are interested in showing how this emotional temper motivates a special transformation of the meaning of the virus responsible for the current pandemic, a transformation that leads us to consider its mutual (and not only parasitic) nature, which will ultimately and retroactively refer to a better determination of the human existence, as essentially linked to the other, as coexistence.